2011
DOI: 10.1177/0886260511421672
|View full text |Cite
|
Sign up to set email alerts
|

Betrayal Trauma

Abstract: Betrayal trauma, or trauma perpetrated by someone with whom a victim is close, is strongly associated with a range of negative psychological and physical health outcomes. However, few studies have examined associations between different forms of trauma and emotional and physical symptoms. The present study compared betrayal trauma to other forms of trauma as predictors of young adults' psychological and physical symptoms, and explored potential mediators. A total of 185 university undergraduate students comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(62 citation statements)
references
References 67 publications
0
60
1
1
Order By: Relevance
“…For the purpose of this study, we only employed nine items relating to interpersonal traumatic events that participants experienced before the age of 18 years. The Brief Betrayal Trauma Survey has been widely used in large survey designs with clinical and nonclinical participants (e.g., Goldsmith, Freyd, & DePrince, ) and has been used as a measure of interpersonal trauma with participants experiencing psychosis (e.g., Stain et al, ). The measure has good construct validity (DePrince & Freyd, ) and test–retest reliability (Goldberg & Freyd, ) and presented good internal consistency in this study (α = .83).…”
Section: Methodsmentioning
confidence: 99%
“…For the purpose of this study, we only employed nine items relating to interpersonal traumatic events that participants experienced before the age of 18 years. The Brief Betrayal Trauma Survey has been widely used in large survey designs with clinical and nonclinical participants (e.g., Goldsmith, Freyd, & DePrince, ) and has been used as a measure of interpersonal trauma with participants experiencing psychosis (e.g., Stain et al, ). The measure has good construct validity (DePrince & Freyd, ) and test–retest reliability (Goldberg & Freyd, ) and presented good internal consistency in this study (α = .83).…”
Section: Methodsmentioning
confidence: 99%
“…High-betrayal traumas, such as physical abuse by a close family member, should have more impact on physical and psychological outcomes than ones low in betrayal, such as being in an earthquake. In support of the theory, some studies have found associations between high- but not low-betrayal trauma and physical and mental health outcomes (Goldsmith, Freyd, & DePrince et al, 2012; Edwards, Freyd, Dube, Anda, & Felitti, 2012). However, these studies have relied on self-reports of physical symptoms, functional status, or mental health.…”
mentioning
confidence: 89%
“…Different trauma types might therefore contribute differently to psychopathology in a way that would be masked by a cumulative trauma index. Indeed, research in non-refugee populations has shown differences in pathology across subtypes of trauma exposure (15). Specifically, traumas involving betrayal have been associated with greater pathology than similar traumas that do not involve betrayal (e.g., seeing a family member attacked by another family member vs. attacked by a stranger; 15).…”
Section: Introductionmentioning
confidence: 99%